Downgrade BI-RADS 4A Patients Using Nomogram Based on Breast Magnetic Resonance Imaging, Ultrasound, and Mammography - Xie, Yamie; Zhu, Ying; Chai, Weimin; Zong, Shaoyun; Xu, Shangyan; Zhan, Weiwei; Zhang, Xiaoxiao (Frontiers in Oncology, 2022)
Objectives Study how to downgrade the BI-RADS 4A patients by constructing a nomogram using R software. Materials and Methods The institutional review board of Shanghai Ruijin Hospital approved the retrospective study and abandoned the requirement to obtain patient approval or written informed consent to review medical records or images. 1717 patients were retrospectively analyzed who underwent preoperative ultrasound, mammography, and magnetic resonance examinations in our hospital from August 2019 to September 2020, and a total of 458 patients of category BI-RADS 4A (mean age, 47 years; range 18-84 years; all women) were included. Multivariable logistic regression was used to screen out the independent influencing parameters that affect the benign and malignant tumors, and the nomogram was constructed by R language to downgrade BI-RADS 4A patients to eligible category. Results 59.6% (273/458) of BI-RADS 4A patients were degraded to category 3. The malignancy rate of these 273 lesions is 1.5% (4/273) (<2%), and the sensitivity reduced to 99.6%, the specificity increased from 4.41% to 45.3%, and the accuracy increased from 63.4% to 78.8%. Conclusion By constructing a nomogram, some patients can be downgraded to avoid unnecessary biopsy.